ASME 2009 Summer Bioengineering Conference, Parts a and B 2009
DOI: 10.1115/sbc2009-206430
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Pulls Microtubules Without Rotating Its Stalk

Abstract: Dynein is a motor protein that hydrolyses ATP and moves toward the minus end of a microtubule (MT). A dynein molecule has one to three heavy chains, each consisting of three domains: a head, a stalk and a tail. ATP is bound and hydrolysed in the head, which has a ring-like structure composed of 6 AAA+ domains. The stalk is an antiparallel coiled-coil, 10–15 nm long, and has a nucleotide-dependent MT-binding domain at the tip (1) (Fig. 1). It has been proposed that the nucleotide-dependent binding affinity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 39 publications
14
41
0
Order By: Relevance
“…Nucleotideinduced conformational change in dynein was found both in vitro (Burgess et al, 2003;Ueno et al, 2008) by 2D averaging from electron microscopy of stained dynein, and in situ (by cryo-electron tomography: Movassagh et al, 2010). The changes in both types of samples are consistent with a model in which dynein moves along the microtubule from the plus end to the minus end.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nucleotideinduced conformational change in dynein was found both in vitro (Burgess et al, 2003;Ueno et al, 2008) by 2D averaging from electron microscopy of stained dynein, and in situ (by cryo-electron tomography: Movassagh et al, 2010). The changes in both types of samples are consistent with a model in which dynein moves along the microtubule from the plus end to the minus end.…”
Section: Introductionsupporting
confidence: 65%
“…1) Dyneins forming a linear array could cause suppression. In this case, pure reconstituted dynein arrays on microtubules (Oda et al, 2007;Ueno et al, 2008) might show the same heterogeneity we have observed in situ. 2) An interaction between radial spoke head proteins and the central pair could be involved.…”
Section: Increase In Atpase Activity From Axoneme To Cross-bridged Cosupporting
confidence: 51%
“…Dynein from sea urchin outer arms and microtubules reconstituted with intact dyneins in the presence and in the absence of ADP.Vi did not show the nucleotide-dependent change of the binding angle of the stalk with respect to the microtubule, supporting the winch model (Ueno et al, 2008) (Fig. 3BE).…”
Section: Force Generation Of a Dynein Headmentioning
confidence: 56%
“…During the ATPase hydrolysis cycle, dynein attaches to and then detaches from the microtubule by the Burgess et al (2003)). (B and E) Averaged images of outer arm dynein from sea urchin sperm reconstituted with microtubules (modified from Ueno et al (2008)). (C and F) Section from averaged tomograms of outer dynein arms from Chlamydomonas flagella (modified from Movassagh et al (2010)).…”
Section: Regulation Of Microtubules Bindingmentioning
confidence: 99%
“…Indeed, a linkage between the γ HC motor unit and the A-tubule that may represent this connection has been directly observed by cryoEM tomography (Oda et al 2007). Furthermore, examination of sea urchin outer arm dynein–microtubule complexes by cryo-positive staining EM revealed a similar connection emanating from the α HC 2 (Ueno et al 2008). …”
Section: An Outer Arm Dynein Mechano-sensormentioning
confidence: 81%